Pattern of Mitral Inflow Velocity due to Left Ventricular Diastolic Dysfunction among Impaired Glucose Tolerance Patients - Bhuiyan, AKM Mohiuddin; Hasan, KAM Mahbub; Moureen, Adneen; Hasan, Md. Kamrul; Zobayer, Md.; Choudhury, Shahnaz (Journal of Current and Advance Medical Research, 2025)
Background: The pattern of mitral inflow velocity may vary due to left ventricular diastolic dysfunction among impaired glucose tolerance. Objectives: The purpose of the present study was to assess the pattern of mitral inflow velocity due to left ventricular diastolic dysfunction among impaired glucose tolerance. Methodology: This cross-sectional study was carried out in the Department of Cardiology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from July 2005 to June 2007 for a period of two (02) years. Patients with impaired glucose tolerance (IGT) patients attending the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh, who fulfilled the selection criteria were included in this study as group A. The apparently healthy persons without cardiovascular disease were taken as group B. All the study subjects underwent 2D and M-mode echocardiography for chamber enlargement, ventricular hypertrophy and ventricular systolic function according to the recommendation of the American Society of Echocardiography. Results: Doppler mitral inflow parameters between groups showed that E-wave 58.94±15.14 vs 71.14±10.60 cm/s, p<0.001, and E/A ratio 1.13±0.46 vs 1.48±0.36, p<0.001 significantly lower in group A, but A-wave 55.32±9.55 vs 49.54±6.93 cm/s, p<0.01 significantly higher in group A compared to group B subjects. Doppler mitral inflow parameters were also compared between LVDD present and absent groups, which showed that E-wave 45.58±5.46 vs 73.42+5.97 cm/s, p<0.001, E/A ratio 0.74±0.12 vs 1.56±0.26, p<0.001, significantly lower in LVDD present group, while A-wave 62.12±6.35 vs 47.96±6.46 cm/s, p<0.001, and DT 224.42±3.53 vs 192.79±8.54 msec, p<0.001) were significantly higher in LVDD present group. Conclusion: In conclusion the pattern of mitral inflow velocity is significantly different due to left ventricular diastolic dysfunction among impaired glucose tolerance patients. Journal of Current and Advance Medical Research, July 2024;11(2):62-67